2006
DOI: 10.1212/01.wnl.0000192129.65677.87
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory, immune, and viral aspects of inclusion-body myositis

Abstract: Muscle biopsies from patients with sporadic inclusion-body myositis (sIBM) consistently demonstrate that the inflammatory T cells almost invariably invade intact (not vacuolated) fibers, whereas the vacuolated fibers are rarely invaded by T cells. This indicates two concurrently ongoing processes, an autoimmune mediated by cytotoxic T cells and a degenerative manifested by the vacuolated muscle fibers and deposits of amyloid-related proteins. The autoimmune features of IBM are highlighted by the strong associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
1
6

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(70 citation statements)
references
References 42 publications
1
62
1
6
Order By: Relevance
“…Alternatively, a beneficial αBC chaperoning effect in s-IBM muscle fibers can also be considered if the αBC binding is to a cytotoxic moiety of AβPP/Aβ. Our studies do not negate the possibility, as was previously suggested [17], that in s-IBM muscle fibers αBC might also be induced by other stressors, for example a yet unidentified virus, which has been proposed to play a role in the s-IBM pathogenesis [reviewed in [1][2][3] and which could be antecedent to the increased expression of AβPP/Aβ.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…Alternatively, a beneficial αBC chaperoning effect in s-IBM muscle fibers can also be considered if the αBC binding is to a cytotoxic moiety of AβPP/Aβ. Our studies do not negate the possibility, as was previously suggested [17], that in s-IBM muscle fibers αBC might also be induced by other stressors, for example a yet unidentified virus, which has been proposed to play a role in the s-IBM pathogenesis [reviewed in [1][2][3] and which could be antecedent to the increased expression of AβPP/Aβ.…”
Section: Discussioncontrasting
confidence: 52%
“…Light-microscopic features of s-IBM muscle biopsies include vacuolated muscle fibers, accumulation of intra-muscle-fiber multiprotein aggregates, and various degrees of lymphocytic inflammation [2]. Two hypotheses regarding the key pathogenic mechanisms involved in s-IBM are: a) an amyloid-β-related myodegenerative process, and b) an immune dysregulation [reviewed in 2,3]. Intriguingly, the s-IBM muscle-fiber phenotype has similarity to the Alzheimer-disease brain, such as accumulations of multiproteinaggregates containing proteins in congophilic alternate conformation, including amyloid-β (Aβ) [2].Reduction of 26S proteasome activity and features of aggresomes were recently demonstrated within s-IBM muscle fibers, and these were modeled in cultured human muscle by experimental overexpression of AβPP [4].…”
Section: Introductionmentioning
confidence: 99%
“…Muscle damage is not related to direct invasion of muscle fibers by the virus, but to an immune-mediated process 39 . Classically, both polymyositis (PM) 40 and inclusion body myositis (IBM) 41 have been associated with HTLV-1 infection. Furthermore, clinicians may also consider ordering HTLV-1 testing in the context of isolated cramps without other features of myopathy and in patients with persistent serum creatine phosphokinase (CK) elevation.…”
Section: Amyotrophic Lateral Sclerosis (Als) Syndromementioning
confidence: 99%
“…Deep tendon reflexes are diminished or abolished but may be normal or even brisk in patients with concomitant HAM/TsP. Other manifestations such as rheumatologic (arthritis, Raynaud's phenomenon), cardiac (myocarditis), and respiratory (pneumonitis) complications are present in HTLV-1-related PM, but they are less frequent than in HTLV-I-seronegative PM 40,41 .…”
Section: Amyotrophic Lateral Sclerosis (Als) Syndromementioning
confidence: 99%
“…By analogy to numerous autoimmune diseases, a viral contribution to the etiology of IBM has been discussed for as long as the condition has been identified 58, 59. Presently, it is not ultimately clear by which exact mechanism(s) viruses may trigger autoimmunity.…”
Section: Pathomechanisms In Ibmmentioning
confidence: 99%